Analysis on mechanical properties of wood plastic composite. (2021) - Bhaskar, K.; Jayabalakrishnan, D.; Vinoth Kumar, M.; Sendilvelan, S.; Prabhahar, M.
Abstract: Wood-plastic composites (WPC) are actually a type of composites made by blending wood particles/flour with polymers. The Mechanical Properties of Wood Plastic Composites primarily is dependent on the makeup of the matrix of its (Polymers), reinforcements (Sawdust), coupling agents, and lubricants. In general, the polymer of the matrix in WPCs is actually made of a single monomer like HDPE, PS, PP, PET, etc. The Objective of the project is actually investigating the physical properties of a Wood Plastic Composite by using polymer blend (a combination of two or maybe more polymer) as a matrix and the effects of its own physical properties of WPC by varying the makeup of the combination at various proportions.